PENYELARASAN STRATEGI BISNIS DAN STRATEGI SISTEM/TEKNOLOGI INFORMASI UNTUK PENINGKATAN KINERJA ORGANISASI - Ardi Hamzah (Universitas Trunojoyo Madura, 2007)
Alignment strategic become one of this topic in informationsystem also represent the issue which still newly and interesting,especially its applying in Indonesia. System/ information technologyproven have keep role important in organizational development andexistency. For that, needed aligment strategic model between strategyof business and strategy of system/information technology inimproving organizational performance. Strategic aligment for companyto reach its target with the support of information system in process ofbusiness to give the real correct management information. To thisconduct, information technology at organization have to in aligmentwith organizational goal. Emporwement and utilization of ability ofsystem/information technology inwroughtly, sinergy andcomprehensive with organizational business strategy to reach for thecompetitif advantage assessed have given the significant contributionto organizational strategic aligment. More high level strategic aligmentbetween strategy of business and strategy of system/informationtechnology, organizational will instruct the information system of matterof crucial to reach for the successful business performance.